Traditional Greek Dance, Positive and Negative Affect, Self-Esteem and Subjective Vitality - Petraki Βασιλική; Digelidis Νικόλαος; Krommydas Χαράλαμπος (Inquiries in Physical Education and Sport, 2019)
Exercise in the workplace as a health promotion tool, has positive effects on the workers, the employers and society in general. Let alone in the hospital, where health professionals and other staff exposed daily to stressors factors. The purpose of the study is to explore whether Greek traditional dance, as a kind of exercise, promotes and enhances dancers’ emotions, subjective vitality and self-esteem. Two hundred employees (Mean age: 44.99 ± 9.75 years) in public health system (health professionals and hospital staff) voluntarily participated in the present study and were randomly assigned to two groups. The experimental group consisted of 100 people (28 men and 72 women) who participated in Greek traditional dance lessons, while the control group consisted of 100 hospital employees (28 men and 72 women). The results showed that the traditional dancers (experimental group) displayed significantly higher scores in positive affect, subjective vitality, self-esteem and lower scores in negative affect compared to the non-dancers (control group). Based on the above, traditional dance seems to improve the quality of life of employees in a hospital setting.